Peningkatan Kemampuan Sosial Melalui Kegiatan Bermain Peran Makro pada Anak Usia 3-4 Tahun di Kelompok Bermain Dharma Wanita Persatuan Kebaron - Lestari, Ira Dwi; Salim, Agus (Indonesian Journal Publisher, 2023)
This research was conducted based on observations that had been made to children in the Playgroup at KB Dharma Wanita Persatuan Kebaron related to social skills in children who still needed stimulation to build their social development. Social skills are very important in the life of early childhood because with social skills children can interact, communicate and socialize with peers and other people around them. From these problems, we need an improvement that can improve a child's social development ability. Children need activities that are very interesting and fun and are activities that are not often done, one of which is role playing. Based on research at KB Dharma Wanita Persatuan Kebaron at the age of 3-4 years, there are 80% of children who are less able to socialize. Due to the lack of this, the researchers used macro role-playing activities to improve children's social skills. The researcher uses classroom action research as one of the research methods to get the expected results. The research was carried out in 2 cycles. One of the actions carried out in a planned and never done before. In the first cycle the percentage value is 70% which means that it has not met the planned target. The researcher continued to provide action in cycle II. After the second cycle of research, the percentage of the average score of children became 85%, so that the average value of the first and second cycles increased. From the results obtained, there is an increase which proves that this research is successful with Macro Role Playing activities that can increase according to the target set by the researcher in social skills.